Clinico-pathological correlates and survival outcomes in 214 resected ampullary adenocarcinomas – are outcomes different in intestinal and pancreatobiliary subtypes with adjuvant gemcitabine?. Issue 3 (March 2020) - Ramaswamy, Anant; Bhandare, Manish; Bal, Munita; Shrirangwar, Sameer; Kataria, Pritam; Majumdar, Swaratika; Swami, Rohit; Rohila, Jitender; Chaudhari, Vikram; Mandavkar, Sarika; Chavan, Neeta; Shrikhande, Shailesh V.; et al.
Abstract: Background: Evidence suggests that intestinal type (IT) and pancreatobiliary (PB) subtypes of ampullary adenocarcinoma (AC) may have different outcomes. The current study evaluated differences in outcomes between these subtypes and the benefit of adjuvant chemotherapy (AT). Methods: A prospectively maintained database of patients who underwent upfront resection for AC from January 2012 to March 2016 was conducted. A dedicated pathologist reported differentiation between IT and PB subtypes. Results: 214 patients were included for analysis: 105 PB subtype and 109 IT subtype. With a median follow up of 46.3 months, estimated 4 year overall survival (OS) was 65.8%. In patients with stage II–III disease, lymph-node ratio (LNR) < 0.2 [Not reached (NR) vs. 30.72 months; p = 0.002], absence of perineural invasion (PNI) (NR vs. 31.61 months; p = 0.032) and AT (gemcitabine – 96.1%) (NR vs. 22.28 months) were prognostic for superior OS. There was no difference in OS between IT and PB subtypes, but both subtypes with stage II–III disease benefitted from AT statistically as compared to observation (IT: NR vs. 28.62 months; PB: 18.46 months vs. 58.09 months; p < 0.001). Conclusions: AC-IT and AC-PB did not have a different OS when treated with resection and adjuvant gemcitabine, though adjuvant therapy benefitted both subtypes individually.